2006
DOI: 10.1002/ejic.200600408
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Half‐Sandwich Ruthenium(II) Complexes as Catalysts in 1,3‐Dipolar Cycloaddition Reactions of Nitrones with Methacrolein

Abstract: Ruthenium complexes of formula [(η6‐arene)Ru(LL*)(H2O)][SbF6]2 (arene = C6H6, p‐MeC6H4iPr, C6Me6; LL* = bidentate chelate chiral ligand with PN, PP or NN donor atoms) have been tested as catalyst precursors for the asymmetric 1,3‐dipolar cycloaddition of nitrones to methacrolein. The reaction occurs quantitatively with perfect endo selectivity and moderate enantioselectivity (up to 74 % ee). The ruthenium aqua complexes can be prepared from the corresponding chlorides, [(η6‐arene)RuCl(LL*)][SbF6]. Dipolarophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 65 publications
(11 reference statements)
1
13
0
Order By: Relevance
“…51 As it was reported, chiral complexes 74b and 74c gave the best 3,4:3,5 regioisomeric ratios, and compounds 97-99 were obtained as unique 3,5-regioisomers. In general, the enantioselectivities were very low, whilst chemical yields were very high or quantitative.…”
Section: Nitronesmentioning
confidence: 60%
“…51 As it was reported, chiral complexes 74b and 74c gave the best 3,4:3,5 regioisomeric ratios, and compounds 97-99 were obtained as unique 3,5-regioisomers. In general, the enantioselectivities were very low, whilst chemical yields were very high or quantitative.…”
Section: Nitronesmentioning
confidence: 60%
“…The asymmetric 1,3‐dipolar cycloadditions of nitrones and methacrolein reported to date have been limited to the preferential formation of the 5‐CHO‐ endo isomer4a,c,d,e or the generation of both 5‐CHO‐ endo and 4‐CHO‐ endo isomers in the moderate preference to the 4‐CHO‐ endo isomer (Scheme ) 4fh. Contrary to these results, our research revealed that the regiochemical outcome of the bis‐titanium chiral Lewis acid catalyzed reaction of N ‐benzyl nitrone and methacrolein was found to be exclusively 4‐CHO‐ endo ‐selective, albeit in quite low yield 9.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, quantitative conversions are achieved at À25 C, in a few hours. Perfect diastereoselectivity for the endo adducts is observed, but only low to moderate enantioselectivity is obtained [37].…”
Section: Dcr Of Nitrones With Enalsmentioning
confidence: 97%